Українізація УСРР у західноукраїнській суспільно-політичній думці 1920 х рр. - Кравець, Данило; Kravets, Danilo (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Проаналізовано ставлення західноукраїнських політичних партій та суспільно-політичних діячів до українізації – національної політики більшовиків у радянській Україні. Розглянуто цю ситуацію крізь призму газетних публікацій, епістолярних матеріалів, резолюцій з’їздів політичних партій.This article based on archival sources, press, diaries and scientific literature analyzes Western-Ukrainian public opinion about Ukrainization - national policy of Bolshevik’s government in Soviet Ukraine. On one hand this policy has been criticized by all liberal press of Galicia and by all local Ukrainian national leaders but on the other hand many viewers underlined a lot of positive moments in this communist’s national policy. For example leader of Taras Shevchenko Scientific Society K. Studynskiy described ukrainization very positively. He was impressed by the level of Soviet Ukraine cities ukrainization. Another titan of Western-Ukrainian V. Mudryj described communist national policy with some level of critic.
Ukrainization of USSR in West Ukrainian Public and Political Opinion in 1920 th.
Keywords: українізація; радянська Україна; національна політика; УНДО; УСРП; Західна Україна; суспільно-політична думка; Ukrainization; national policy; Soviet Ukraine; UNDO; USRP; Western Ukraine; public and political opinion